Peran Administrasi Publik Dan Komunikasi Publik Dalam Membangun Kolaborasi Antara Kelompok Masyarakat (Pokmas Mulya Abadi) Dan Pemerintah Guna Pembangunan Kelurahan - Ulva Roifatul Lailin; Nik Haryanti; Rio Septyan Ardiansyah (Public Service and Governance Journal, 2024)
Village development is an important part of efforts to improve the quality of life of urban communities. This research examines the role of public administration and public communication in building collaboration between community groups and the government in sub-district development. This research is very important because the success of sub-district development is very dependent on collaborative relationships between the government and community groups. The aim is not only to find things that influence this cooperation, but also to show useful methods for increasing community participation in sub-district development. This research uses a qualitative approach that collects data through participant observation, document analysis, and in-depth interviews. This research includes searching for data information through relevant officials or a team of facilitators on community empowerment activities in physical and non-physical work, examining policies and regulations related to community empowerment, and direct observation of Mulya Abadi Pokmas activities in Bendogerit Village, Blitar City. Next, the data was analyzed using a thematic approach to find patterns and themes in public communication, public administration, and collaboration between society and government. It is hoped that the results of this research will provide a better understanding of the dynamics of collaboration in village development between government groups and communities. Intended outcomes also include policy suggestions for increasing the effectiveness of collaboration, practical guidance for building strong relationships between government and community groups, and theoretical contributions to improve our understanding of public administration and public communication.